Analisis Dampak Kenaikan Tarif Pajak Pertambahan Nilai (PPN) 11% Terhadap PT Sari Kencana - Fitriani, Atika; Cindy Fredicia Putri; Dwi Fionasari; Putri Dasti S Harahap; Sarifah Aini Hasibuan (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2025)
This research examines the impact of increasing the Value Added Tax (VAT) rate to 11% on PT operations. Sari Kencana, a transportation services company. The aim of the research is to analyze the influence of this policy on ticket sales, market demand, and the company's adaptation strategy. The research uses qualitative methods with descriptive analysis, collecting primary data through interviews and observations, as well as secondary data from related documents. The research results show that the increase in VAT rates affects operational costs and people's purchasing power, which results in a decrease in the number of customers. To overcome these challenges, PT Sari Kencana adjusts ticket prices, optimizes operational costs, improves service quality, and utilizes technology, such as developing ticket ordering applications. This strategy helps companies maintain competitiveness and customer loyalty, despite pressures due to fiscal policy.